Induction of betaine-γ-aminobutyric acid transport activity in porcine chondrocytes exposed to hypertonicity - de Angelis, Elena (Blackwell Science Inc, 1999)
1. We measured the rates of uptake of selected amino acids and betaine by primary cultures of chondrocytes from porcine articular cartilage after the cells had been incubated in ‘isotonic’ (0·3 osmol l(−1)) or hypertonic (0·5 osmol l(−1)) media. 2. Na(+)-dependent uptake of methylaminoisobutyric acid increased rapidly when the cells were exposed to hypertonic conditions, reached a peak after 6-9 h, and then gradually decreased so that after 24 h it was only slightly above the control value. Conversely, (Na(+)+ Cl(−))-dependent influx of γ-aminobutyric acid (GABA) remained low for the first 9 h of hypertonic incubation, but then increased markedly to reach a plateau value after 24-30 h. Betaine influx also increased in cells incubated in hypertonic medium, being mainly Na(+) dependent after 6 h, but (Na(+)+ Cl(−))-dependent after 24 h. 3. This pattern indicates that exposure of the chondrocytes to hypertonicity induces first amino acid transport system A and then, as this decreases again, betaine-GABA transport activity. 4. Induction of betaine-GABA transport activity did not require continuous exposure of chondrocytes to hypertonicity; but the magnitude of the increase measured at the end of a 24 h incubation period was proportional to the length of time the cells had been exposed to hypertonicity during the 24 h. 5. Isolation and culture of chondrocytes in 0·4 osmol l(−1) medium, instead of 0·3 osmol l(−1,) significantly increased their betaine-GABA transport activity, but not their system A activity. 6. Induction of betaine-GABA transport activity was prevented by addition of either actinomycin D or cycloheximide to the medium, but no mRNA for the betaine-GABA transporter known as BGT-1 was detected by Northern blot analysis of extracts of chondrocytes.